2021
DOI: 10.1590/1413-81232021269.2.07762020
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health and hearing disorders: study of the Brazilian hearing-impaired population

Abstract: Hearing impairment (HI) is one of the most impacting handicaps related to social life, and 21% have intense limitation compromising daily activities. However, few studies have investigated SRH in HI. This article aims to verify the association between HI and SRH and factors related to hearing characteristics. Cross-sectional study data from National Health Survey (NHS, 2013) conducted with 1,100 hearing impaired adults (≥18 years old). The outcome was SHR, categorized as good or poor. Poisson regression with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Additionally, after access to hearing aids and/or rehabilitation, they develop coping strategies to integrate with the community, such as sign language, orofacial reading, etc. Moreover, hearing impairment is a type of "silent impairment" that does not impede physical mobility and integration into the community, even though, at times, spoken messages may not be understood [22,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, after access to hearing aids and/or rehabilitation, they develop coping strategies to integrate with the community, such as sign language, orofacial reading, etc. Moreover, hearing impairment is a type of "silent impairment" that does not impede physical mobility and integration into the community, even though, at times, spoken messages may not be understood [22,32].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, information about the impairments was obtained through self-reports and depended on the personal understanding of each participant and their values, conception of health, and culture [5,22]. In this regard, a review study indicated the significance of standardized definitions of impairments, as there is considerable variation in self-reports about impairments during census [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the high burden of hearing loss and its adverse influence on the quality of life, hearing loss affects patients’ SRH and psychosocial ( Jayakody et al, 2022 ). Patients with hearing loss may have poor SRH due to limited social participation and disability in daily activities in the absence of hearing aids ( Anderle et al, 2021 ). A Brazilian study found that the odds of reporting poor SRH in peers who perceived hearing loss as a health problem were 3.72 times higher compared with peers who failed to perceive hearing loss as a health problem ( Guia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders adjusted in the multivariable model were age, sex, socioeconomic position (occupation, education, household income), smoking [ 35 , 36 ], alcohol use [ 36 , 37 ], number of comorbidities [ 38 , 39 ] and self-rated health [ 40 , 41 ]. Occupation referred to the occupation that participants had for the longest period in their life.…”
Section: Methodsmentioning
confidence: 99%